Auditory evoked potentials as yardstick for tinnitus - Banerjee, Shrutinath; Paul, Nilanjan; Chatterjee, Indranil; Das, Ishita; Das, Rima; Debnath, Sucheta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Aiming to evaluate the recent theoretical postulates on tinnitus underscoring the role of thalamocortical neural tracts, the present study: explores middle latency response (MLR) as a possible physiological measure of tinnitus: thus investigates the predicted exaggeration of Pa-Na, Na-Pb interpeak amplitudes in tinnitus patients and; explores middle latency response (MLR) as a prognostic indicator of tinnitus retraining therapy (TRT), thus evaluates possible decrease in Pa-Na and Na-Pb amplitude after 2 weeks exposure to tinnitus retraining therapy. Methods: An experimental group was constructed by randomly assigning 30 patients with mean age 38.5 years and complaining of debilitating tinnitus but with normal hearing for the study. MLR was administered on patients with normal auditory brainstem response (ABR) and otoacoustic emission (OAE) both pre- and post-tinnitus retraining therapy. Results: Results demonstrated no significant effect on Pa, Na and Nb absolute and interpeak latencies. However, significantly exaggerated Pa-Na and Na-Pb interpeak amplitudes between experimental and control groups as well as pre and post therapeutic groups were found. Conclusions: This proves that MLR may adequately reflect thalamocortical hyperactivity in cases with distressing tinnitus and demonstrable improvement post TRT warrants the use of MLR as its prognostic indicator.